A Valid Approach in Refractory Glossodynia: A Single-Institution 5-Year Experience Treating with Japanese Traditional Herbal (Kampo) Medicine. (7th October 2013) - Okamoto, Hideki; Chino, Atsushi; Hirasaki, Yoshiro; Ueda, Keigo; Raimura, Masaki; Namiki, Takao
Abstract : Glossodynia is often refractory to conventional medicine, and there is only limited evidence to guide clinicians in its management. Patients with refractory glossodynia are often introduced to Japanese traditional herbal (Kampo) medicine experts under such circumstances because Kampo medicine has become known in Japan to be effective in treating a wide variety of symptoms refractory to conventional medicine. Herein, we report our single-institution 5-year experience treating patients with Kampo medicine for primary glossodynia that was refractory to conventional medicine. We found that 69.2% of patients reported a beneficial effect of Kampo medicine on glossodynia, and the average onset of improvement was 8.0 ± 7.7 weeks after starting Kampo treatment. The top two frequently used Kampo medicines for glossodynia were seinetsuhokito and mibakuekkito among high responders who showed a decrease of severity by 50% or more. The top four most overlapped herbs among effective Kampo medicines for glossodynia were Glycyrrhiza Root, Ginseng Root, Hoelen, and Atractylodes (lancea) Rhizome, which compose an essential Kampo prescription called shikunshito. Although more research is required to further clarify the effectiveness of Kampo medicine, it has valid efficacy even in cases of glossodynia that remain incurable by conventional treatments.